Algal Community Structure of the Yalour Mausoleum, Cemetery of La Plata, Buenos Aires, Argentina - Gómez de Saravia, Sandra Gabriela (2018)
Biologicla communities that form biofilms on buildings and monuments can not only discolour the surface, but also produce physical and chemical alterations [1] Althought the type of organisms that colonize the facades of cement constructions is diverse, the analyzes carried out "In situ" reveal that algaeare one of the initial and main colonizers [2]. The algae cancause bichemical deterioration , since they produce, like fungi, metabolites of a predominantly organic nature. The Cemetery of La Plata, founded by Benoit in 1887, hsa inits interior mausoleums and notable monuments of various styles worthy of patrimonial protection. One of them is the Yalour mausoleum that is uniformly covered by a black patina, with conspicuous spots of lighter shade. Various chemicals with biocidal activity are commonly added to interior and exterior to provide protection of algal growth. In order to select compounds that prevent and control biofilm formation , it is necessary to know what organisms generate it, how they are structured and what physiologyical activity they present.For this reason,the aim of this work wsa to characterize, from hrbioloogicla point of view, the biofilm developed on the mausoleum.